The Ohakunea group in Tasmania, with description of Colonomyia tasmanica sp. n. (Diptera: Sciaroidea). - Jaschhof, Mathias; Jaschhof, Catrin (Contributions to Entomology = Beiträge zur Entomologie, 2008)
The Ohakunea group of genera (unplaced to any family of the Sciaroidea) is present in Tasmania with three species: Ohakunea australiensis Colless, which is newly recorded, Colonomyia albicaulis Colless, and Colonomyia tasmanica sp. n. The new species, which appears to be endemic to Tasmania, is the closest relative of Colonomyia rakelae Hippa & Jaschhof from New Guinea. New arguments presented here support the hypothesis that the Australasian species of Colonomyia form a clade (= Colonomyia sensu stricto) distinct from the congeneric species in the Neotropical region. The complex structure of male and female terminalia of Colonomyia s. str. spp. possibly present an example of lock-and-key that is documented and discussed. Keywords Diptera, Sciaroidea, Ohakunea group, Colonomyia, new species, Tasmania. Nomenclatural Acts tasmanica Jaschhof & Jaschhof, 2008 (Colonomyia), spec. n.